A digital manipulative for embodied "stage-narrative" creation - Sylla, Cristina (2014)
This paper presents a study of the use of a digital manipulative developed to promote creative narrative construction and storytelling. The study was carried with 27 groups of preschoolers, of five years of age, who interacted with the digital manipulative during free-play time, during a period of six months. The study sought to assess aspects of children’s embodiment of the narratives, and how they shaped the creation of stories. We observed that by using the digital manipulative, children’s narrative construction occurred in two levels, as children shared the stage, (controlling the characters, the location, the props, and the nature elements) and simultaneously performed on this stage. The sharing of the input devices (blocks) gave children equal control of the performance and orchestration of the story, while promoting and supporting peer collaboration. We conclude that the digital manipulative enables the performance of what we call embodied stage-narratives, promoting children’s imagination and creative thinking, as well as fostering early literacy skills and metalinguistic awareness.